Reflecting on the balance between theory and practical grades of engineering students — A case study - Swart, James; Olwagen, Lienie; Greyling, Cameron; Luwes, Nicolaas (IEEE Xplore: IEEE AFRICON, 2017)
Universities of Technology must enable students to acquire the necessary knowledge (theory), workplace skills (practice), and graduate attributes (theory and practice) needed to meet the needs of industry, business and community. Reflective practice may involve the thoughtful consideration of an academics own experiences in enhancing the fusion of theory and practice in an engineering curriculum. This fusion is currently an important criterion for Universities of Technology who may face increased pressure to improve their throughput rates. This paper aims to answer the following research question: “What balance currently exists between the practical and theoretical success of undergraduate students in a number of different engineering disciplines at a University of Technology”? Reflecting on the current balance that exists and its implications may assist academics in changing their pedagogy to include more effective ways of fusing theory and practice. A post-facto study is employed along with descriptive statistics involving quantitative analysis of the collected data. Results do indicate that undergraduate engineering students are more adept at completing the practical assessments scheduled in a laboratory, suggesting that more time on practice should be scheduled along with practical experiments that promote critical thinking and problem solving skills.
Conference Proceedings
Keywords: laboratory; classroom; attributes; fusing